Analysis of Disaster Management Policy Implementation in the Case Study Areas of Pemenang Barat Village and Malaka Village - Suriadi Ardika; Muazar Habibi; Kosim Kosim (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Pemenang Barat Village and Malaka Village have a high level of vulnerability to earthquakes, tsunamis, and landslides. This condition encourages the implementation of cross-village cooperation through Joint Village Head Regulation (Permakades) Number 1 of 2022 concerning Regional Disaster Management. This study aims to analyze the implementation of this policy using the Van Meter and Van Horn implementation model. The approach used was descriptive qualitative, involving eight key informants representing the Regional Disaster Risk Reduction Forum (FPRBK), village government, and community. Data analysis was conducted using NVivo 12 Pro and Xmind 2025 software. The results show that policy implementation has proceeded with varying degrees of effectiveness in each model component. The policy objectives and standards are understood, but there are still differences in perception and limited technical understanding. Resources, especially budget and human resources, are not optimal; inter-organizational communication is informal and lacks routine coordination; and implementers demonstrate high motivation but remain dependent on leadership direction.